Project management for engineering and construction a life-cycle approach - Oberlender, Garold D.; Spencer, Gary; Lewis, Rose Mary (New York McGraw-Hill, 2022)
This is a new edition of a textbook for project management courses for civil engineering, construction engineering and management, and architecture academic programs. The addition of the new co-authors with diversified experience in the project management field and the new organization of the book are designed to increase market share over the competition.
Electronic reproduction
Keywords: Engineering -- Management; Electronic books